Determinants of left ventricular diastolic function-The Cardiovascular Risk in Young Finns Study - Heiskanen JS; Ruohonen S; Rovio SP; Kytö V; Kähönen M; Lehtimäki T; Viikari JSA; Juonala M; Laitinen T; Tossavainen P; Jokinen E; Hutri-Kähonen N; et al. (WILEY, 2022)
Decreased left ventricular (LV) diastolic function is associated with increased all-cause mortality and risk for a heart failure. The determinants of LV diastolic function have been mainly studied in elderly populations; however, the origin of LV heart failure may relate to the lifestyle factors acquired during the life course. Therefore, we examined biochemical, physiological, and lifestyle determinants of LV diastolic function in 34-49-year-old participants of the Cardiovascular Risk in Young Finns Study (Young Finns Study). In 2011, clinical examination and echocardiography were performed for 1928 participants (880 men and 1048 women; aged 34-49 years). LV diastolic function was primarily defined using E/e-ratio (population mean 4.8, range 2.1-9.0). In a multivariate model, systolic blood pressure (P < 0.005), female sex (P < 0.005), age (P < 0.005), waist circumference (P = 0.024), smoking (P = 0.028), serum alanine aminotransferase (P = 0.032) were directly associated with E/e-ratio, while an inverse association was found for height (P < 0.005). Additionally, a higher E/e-ratio was found in participants with concentric hypertrophy compared to normal cardiac geometry (P < 0.005). Other indicators of the LV diastolic function including E/A-ratio and left atrial volume index showed similarly strong associations with systolic blood pressure and age. In conclusion, we identified systolic blood pressure, waist circumference and smoking as modifiable determinants of the LV diastolic function in the 34-49-year-old participants of the Young Finns Study.